2020
DOI: 10.1002/iid3.390
|View full text |Cite
|
Sign up to set email alerts
|

The BTLA and PD‐1 signaling pathways independently regulate the proliferation and cytotoxicity of human peripheral blood γδ T cells

Abstract: Background B‐ and T‐lymphocyte attenuator (BTLA) and programmed cell death‐1 (PD‐1) inhibit γδ T cell homeostasis and activation. This study aimed to determine whether BTLA and PD‐1 signaling pathways were convergent or independent in human peripheral blood γδ T cells. Herein we demonstrate that the signalings of BTLA and PD‐1 regulated proliferation and cytotoxicity of human γδ T cells, respectively. Methods Human peripheral blood γδ T cells were cultured with inactivated Jurkat cells in the presence of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 44 publications
(54 reference statements)
0
25
0
Order By: Relevance
“… 202 The expression of BTLA was found to be significantly increased in pleural effusion samples from patients with lung cancer, which is an indicator of tumor aggressiveness. 203 Therefore, BTLA, as an inhibitory molecule for immune regulation, has broad research prospects. At present, research on BTLA and HVEM inhibitors is still in the preclinical stage, and it is expected that related drugs will be launched as soon as possible and enter into clinical research verification.…”
Section: Ics On T Cellsmentioning
confidence: 99%
“… 202 The expression of BTLA was found to be significantly increased in pleural effusion samples from patients with lung cancer, which is an indicator of tumor aggressiveness. 203 Therefore, BTLA, as an inhibitory molecule for immune regulation, has broad research prospects. At present, research on BTLA and HVEM inhibitors is still in the preclinical stage, and it is expected that related drugs will be launched as soon as possible and enter into clinical research verification.…”
Section: Ics On T Cellsmentioning
confidence: 99%
“…PD-1 is highly expressed in exhausted T cells and is associated with impaired effector function and increased apoptosis ( He and Xu, 2020 ). It was reported that PD-1 signaling pathways could inhibit the cytotoxicity of human γδT cells ( Hwang et al., 2021 ). Moreover, the weights of the spleens in the infected γδTCR KO mice were decreased implied that γδT cells might promote immune response in the spleen of P. yoelii NSM infected mice as found in P. berghei XAT infection ( Inoue et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, BTLA was highly expressed by Vδ2 + cells in the lymph nodes of patients with lymphoma, and could suppress their proliferation upon ligation by HVEM on primary tumors [ 59 ]. The importance of BTLA in suppressing human γδ T cell proliferation was recently confirmed [ 60 ]. The role of BTLA in MAIT cells or human NKT cells has not been investigated.…”
Section: Btlamentioning
confidence: 98%